2020
DOI: 10.2147/idr.s267997
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tuberculosis in Patients with Primary Myelofibrosis During Ruxolitinib Therapy: Case Series and Literature Review</p>

Abstract: Background: The selective Janus-activated kinase inhibitor ruxolitinib (rux) is now widely used to treat myelofibrosis and polycythemia vera due to its remarkable effect of reducing splenomegaly and improving constitutional symptoms. With opportunistic infections secondary to rux constantly reported; however, an increasing number of studies have begun to investigate the mechanism and underlying immunosuppressive effect of rux. Case Presentation: We report two cases of tuberculosis (TB) in primary myelofibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…TB frequently raises the possibility of myelofibrosis among non-hematopoietic diseases, so clinicians must carefully monitor hospitalized patients with preexisting chronic myeloproliferative disorders. Some authors have reported greater severity of TB and exacerbation of myelofibrosis in patients treated with ruxolitinib, a kinase inhibitor that is widely used to treat myelofibrosis and polycythemia [ 21 ].…”
Section: Rare Hematological Manifestations In Active Tbmentioning
confidence: 99%
“…TB frequently raises the possibility of myelofibrosis among non-hematopoietic diseases, so clinicians must carefully monitor hospitalized patients with preexisting chronic myeloproliferative disorders. Some authors have reported greater severity of TB and exacerbation of myelofibrosis in patients treated with ruxolitinib, a kinase inhibitor that is widely used to treat myelofibrosis and polycythemia [ 21 ].…”
Section: Rare Hematological Manifestations In Active Tbmentioning
confidence: 99%